Sword of Attila - Gibbins, David J. L. (Total war Rome, 2015)
"Sword of Attila begins with the fall of Carthage to the Vandals in AD 439. Rome has already been sacked by the Goths, Britain has been abandoned and the empire in the west is feeling the brunt of barbarian invasions laying waste to the provinces and leading to uneasy alliances with Germanic warlords. As the last remaining Romans flee Africa, a new and more ominous threat emerges, to Romans and their new allies alike - a power from the east like no other since the days of the Persian empire, the Hun army under their general Attila. Can a small band of Roman officers, steeped in the tradition of the old ways, admirers of Polybius and Scipio and Caesar, bring back to Roman arms the glory that once made her great? Or is the idea of Rome now lost to history, a Rome where every second legionary is a barbarian, where it is the new warlords who see themselves as the true inheritors of Roman military glory? Inspired by Total War: Rome II, from the bestselling Total War series, Sword of Atilla is the second installment in an epic series of novels. Only one final battle will tell, a battle that the last dying Sibyl had foretold would see the earth dry up and the rivers be replaced with torrents of gore, where the victors would be the ones who drank their own blood .."--